Discrepancy between self‐assessments and standardised tests of vision and hearing abilities in older people living at home: an ROC curve analysis. Issue 23 (3rd September 2015) - Haanes, Gro Gade; Kirkevold, Marit; Hofoss, Dag; Eilertsen, Grethe
Abstract : Aims and objectives: To determine whether there is consistency between self‐assessments and standardised tests of vision and hearing abilities in older people. Background: Home‐based detection of vision and hearing impairments in older people are generally based on self‐assessments of vision and hearing abilities. Design: Cross‐sectional descriptive study. Methods: Receiver operating characteristic analysis was used to compare self‐assessments of vision and hearing abilities with a gold‐standard test. The vision and hearing abilities of 93 people aged ≥80 years in the home‐care setting were screened with a LogMAR chart, a pure‐tone audiometer, and a self‐assessment screen. Results: Comparison of findings using the cut‐off points on the self‐assessment scale with those of the gold‐standard tests yielded 40 false negatives for vision and 18 false negatives for hearing, indicating that a significant proportion of older people report their vision and hearing abilities as being good when standardised tests indicate that they are not. Alternative cut‐off points on the self‐assessment scale were tested, but no cut‐off point was found to provide a sound basis for identifying vision and hearing impairments. Conclusion: The area under the receiver operating characteristic curve for self‐assessment of vision was 69%, indicating that the self‐assessment questions constituted a poor test. It appears that results from self‐assessments cannot be relied upon to accurately identify visual acuity. The area under the receiver operating characteristic curve for the self‐assessment of hearing was 73%, which may therefore be considered a "fair" test. However, self‐assessment of hearing is still insufficient for detecting hearing impairment. Relevance to clinical practice: Vision and hearing abilities are crucially important to managing daily living. In addition to treatments for suppressing the further development of existing diseases, standardised tests could be a good starting point for health prevention and promotion. Nurses should apply standardised tests to detect sensory impairments in older people.